Ethnomedicinal Uses of Plants from Kapurkot, Salyan District, Nepal - Aryal, Puspa; Pathak, Mitra Lal; Sharma, Gopal; Dahal, Damodar (Journal of Plant Resources, 2022)
The present study aims to document the traditional knowledge of medicinal plants of Kapurkot rural municipality of Salyan District, Karnali province, Nepal. Ethno medicinal information was collected through interview with 40 respondents from Mulpani, Sallyan District. Altogether 59 ethnomedicinal plant species are used for the remedies of different health ailments. Respondents of the age group 25-35 years were found actively participating in this survey. Zingiberaceae as well as the Lauraceae family were found to have the highest number of species used for ethno-medicinal purposes. On the basis of their habit, herb species are found to be highly dominated. The recorded 59 ethnomedicinal plants were used in the treatment of various diseases such as cuts and wounds, skin diseases, fever, cough, boils, burns, common cold, etc. From this study, mainly common cold and cough are mostly recovered ailments from medicinal plant species. The study is mainly based on the experienced knowledge and information which they gain from their elders, mainly from grandparents, which might pass from generation to generation. This current study reveals that Zanthoxylum armatum (Timur), Cinnamomum tamala (Tejpaat) and Zingiber officinale (Adhuwa) are respectively found to be highly traded medicinal plants of the study area. For the preservation of ethnomedicinal plants species as well as their traditional knowledge, different conservation activities should be practiced. Such gained information and knowledge should be passed from generation to generation and encourage them to preserve for sustainable use of traditional documentation.